Impact of climate warming on vegetation cover: positive effects of native artiodactyla vs. grazing pressure in Alborz Protected Area - Salmanpour, Farid; Shakoori, Zahra; Keshtkar, Mostafa; Kia, Mehdi; Sayahnia, Romina (Frontiers in Conservation Science, 2025)
IntroductionClimate warming, combined with grazing pressures, poses significant challenges to vegetation cover and ecosystem stability. In particular, livestock grazing is a primary factor in vegetation degradation, adversely affecting plant diversity, soil health, and key ecological interactions.MethodsThis study investigates the impact of grazing on vegetation in the Alborz region of Iran, focusing on the comparison between native herbivores (Artiodactyla) and livestock in the Central Alborz Protected Area (CAPA). We utilized 30 years of NDVI (Normalized Difference Vegetation Index) data from May to June (1994–2024) to assess vegetation dynamics and evaluate the influence of climate and grazing. ANOVA, Pearson correlation, and regression analyses were performed to identify relationships between vegetation cover, climate variables (temperature and rainfall), and grazing intensity.ResultsResults show a significant increase in vegetation cover, with Golestanak (without livestock) exhibiting a stronger positive response to climate variables (R² = 65%), while Zānoos (higher livestock density) showed greater variability (R² = 58%). Vegetation in Golestanak demonstrated a more significant positive correlation with temperature and rainfall, reflecting resilience to climatic stressors and the beneficial effect of moderate grazing by native Artiodactyla. In contrast, Zānoos showed more fluctuation in vegetation trends due to high livestock grazing pressure.DiscussionThis study highlights that while climate warming can positively affect vegetation cover, intensive livestock grazing can impede these gains, underlining the importance of adaptive management strategies for maintaining ecosystem health.